Implementation and Evaluation of a Ward-Based eLearning Program for Trauma Patient Management. Issue 1 (January 2016) - Curtis, Kate; Wiseman, Taneal; Kennedy, Belinda; Kourouche, Sarah; Goldsmith, Helen
Abstract : The majority of trauma nursing education is focused on the emergency phases of care. We describe the development and evaluation of a trauma eLearning module for the ward environment. The module was developed using adult learning principles and implemented in 2 surgical wards. There were 3 phases of evaluation: (1) self-efficacy of nurses; (2) relevance and usability of the module and; (3) application of knowledge learnt. The majority indicated they had applied new knowledge, particularly when performing a physical assessment (85.7%), communicating (91.4%), and identifying risk of serious illness (90.4%). Self-efficacy relating to confidence in caring for patients, communication, and escalating clinical deterioration improved ( p = .023). An eLearning trauma patient assessment module for ward nursing staff improves nursing knowledge and self-efficacy.